Implementation of the Merdeka Curriculum at Madrasah Tsanawiyah in Aceh Tamiang, Indonesia - Zikriati Zikriati; Aini Safitri; Danil Zulhendra; Rouyan Nurazan Mohmad; M. Riski Fadillah (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2024)
This study examines the planning, implementation, and evaluation processes of the Merdeka curriculum, with a particular focus on the integration of Arabic language teaching at Madrasah Tsanawiyah in Aceh Tamiang, Indonesia. This study utilized a qualitative multi-case approach, focusing on three public madrasah's and one private madrasah. Data were collected through observations, interviews, and document analysis, with respondents comprising 20 seventh-grade Arabic and general subject teachers, four madrasah principals, four curriculum deputies, and four madrasah operators. Findings reveal that the Merdeka curriculum planning, implementation, and evaluation at Madrasah Tsanawiyah in Aceh Tamiang varied across institutions. While some schools demonstrated systematic approaches, disparities emerged in teacher training patterns, readiness for 21st-century skills, and the availability of digital education facilities. These challenges hindered the effective implementation of the curriculum and resulted in the absence of a clear evaluation framework. This study recommends that the government and education policymakers enhance teacher training distribution, improve digital education infrastructure, increase teacher welfare, and establish structured evaluation frameworks to optimize curriculum implementation in addressing global challenges.